PATH-16. Noninvasive diagnosis of gliomas through CSF cfDNA sequencing in pediatric and adolescent and young adult (AYA) patients. (3rd June 2022) - Hill, Katherine; Miller, Alexandra M; Li, Bryan Kincheon; Bouvier, Nancy; Li, Shanita; Alano, Tina; Doe-Tetteh, Seyram; Huereca, Claudia; DiNapoli, Sara; Lee, Alex; Szalontay, Luca; Riviere-Cazaux, Cecile; et al.
Abstract: PURPOSE: A subset of pediatric, adolescent and young adult (AYA) gliomas are located in the brainstem, eloquent locations, or present with diffuse/leptomeningeal disease, and are associated with high risk and low yield of biopsy. At the same time, accurate molecular diagnosis is necessary to direct optimal therapy. In such cases, analysis of cell free DNA (cfDNA) form cerebral spinal fluid (CSF) may represent a diagnostic alternative to biopsy. METHODS: We investigated the utility of CSF cfDNA sequencing through a stepwise approach, using clinically validated, targeted molecular assays. Testing was performed using a broad hybrid capture next generation sequencing assay (MSK-IMPACT) and subsequent targeted digital droplet PCR in a subset of cases. RESULTS: We analyzed 17 CSF samples from 17 pediatric (n=6) and AYA (n=11) glioma patients with primary or recurrent disease. Thirteen had tumors located within the brainstem, and four had leptomeningeal involvement. Somatic alterations were detected in 12/17 samples (71%). In 3/4 patients with leptomeningeal involvement, cfDNA testing revealed a BRAF fusion consistent with the diagnosis of diffuse leptomeningeal glioneuronal tumor (DLGNT). Among the 13 patients with brainstem involvement, four had somatic H3 K27M mutations, three had IDH mutations, and one had TP53 and ATRX mutations; five patients had no detectable mutations. CONCLUSION: In our analysis, we found that established glioma hotspot mutations were able to be detected within the CSF. We propose that in patients for whom tissue biopsy is high risk, not feasible, or tissue was nondiagnostic, CSF cfDNA sequencing has a substantial diagnostic yield and should be considered as a valuable novel diagnostic tool. Ongoing research is aiming to further increase the sensitivity of cfDNA testing, especially in patients with very low levels of CSF cfDNA.